2018
DOI: 10.1186/s12872-018-0900-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of glycemic status and segmental left ventricular wall thickness in subjects without prior cardiovascular disease: a cross-sectional study

Abstract: BackgroundLeft ventricular (LV) hypertrophy and changes in LV geometry are associated with increased cardiovascular mortality. Subjects with type 2 diabetes have an increased risk of such alterations in cardiac morphology. We sought to assess the association of glycemic status and LV wall thickness measured by cardiac magnetic resonance (CMR), and potential interactions of hypertension and diabetes.MethodsCMR was performed on 359 participants from a cross-sectional study nested in a population-based cohort (KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Long-term studies have unequivocally demonstrated the development of left ventricular hypertrophy in metabolic syndrome; 43 however, even prolonged pre-diabetes provides a constellation of physiological derangements that favor left ventricular remodeling in rats 44 , 45 and humans. 46 In fact, fructose alone, albeit at a higher concentration (60%), causes cardiac hypertrophy in mice after 10 weeks. 47 Moreover, direct fructation of structural proteins 29 or alterations in sympathetic cardiac innvervation 48 have been associated with diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term studies have unequivocally demonstrated the development of left ventricular hypertrophy in metabolic syndrome; 43 however, even prolonged pre-diabetes provides a constellation of physiological derangements that favor left ventricular remodeling in rats 44 , 45 and humans. 46 In fact, fructose alone, albeit at a higher concentration (60%), causes cardiac hypertrophy in mice after 10 weeks. 47 Moreover, direct fructation of structural proteins 29 or alterations in sympathetic cardiac innvervation 48 have been associated with diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of fructose plus high salt even, in the short term, in the present study results in mildly elevated non-fasting blood glucose and a depressed glucose:insulin ratio consistent with insulin resistance similar to human pre-diabetes. Long-term studies have unequivocally demonstrated the development of left ventricular hypertrophy in metabolic syndrome; 43 however, even prolonged pre-diabetes provides a constellation of physiological derangements that favor left ventricular remodeling in rats 44,45 and humans. 46 In fact, fructose alone, albeit at a higher concentration (60%), causes cardiac hypertrophy in mice after 10 weeks.…”
Section: Left Ventricular Diastolic Dysfunctionmentioning
confidence: 99%
“…Biochemical parameters were assessed in both KORA studies, KORA F4 and KORA FF4, using standard methods described previously. [ 8,24 ]…”
Section: Methodsmentioning
confidence: 99%
“…In SHIP-TREND-0, cardiac MR imaging was performed on a 1.5 Tesla MR system (Magnetom Avanto; Siemens Medical Systems, Erlangen, Germany) [11, 14] and in KORA FF4, on a 3 Tesla MR system (Magnetom Skyra; Siemens Medical Systems, Erlangen, Germany) [15, 16]. In both studies imaging of cardiac function and morphology was performed using cine steady-state free precession (cine-SSFP) sequences.…”
Section: Methodsmentioning
confidence: 99%